Pamudi Media Assisted by Index Card Match: An Innovative Science Learning Effort to Strengthen Students' Cooperation Character - Rahmawati, Isna Rizkita; Untari, Esti; Surayanah, Surayanah (Universitas Negeri Malang, 2024)
Science learning in schools is synonymous with students' learning process skills, which include critical thinking and reasoning, as well as cooperation and respect for the opinions of others. The selection of learning media is necessary to meet the learning needs of students by providing meaningful learning experiences. The purpose of this research and development is to develop PAMUDI media